Graphene Nanoplatelets in Epoxy System: Dispersion, Reaggregation, and Mechanical Properties of Nanocomposites. (17th November 2015) - Wei, Jiacheng; Atif, Rasheed; Vo, Thuc; Inam, Fawad
Abstract : The use of graphene nanocomposites in advanced applications has attracted much attention in recent years. However, in order to substitute traditional epoxy reinforcements with graphene, there are still some issues like dispersion, homogenization, and reaggregation. In this paper, graphene bundles dispersed in two-component epoxy system by bath sonication, dispersion state, and reaggregation behavior of graphene in this system have been studied. Light transmittance in ultraviolet-visible spectroscopy has been used to quantify the reaggregation by a series of controlled experiments. After 18 mins sonication of 0.005 wt% graphene dispersion at 20°C, the light transmittance decreased from 68.92% to 54.88% in liquid epoxy and decreased from 72.80% to 46.42% in hardener; while increasing the temperature from 20°C to 60°C, the light transmittance in liquid epoxy decreased from 65.96% to 53.21% after 6 mins sonication. With the incorporation of 0.3 wt% graphene, the tensile strength of nanocomposites increased from 57.2 MPa to 64.4 MPa and the storage modulus increased from 1.66 GPa to 2.16 GPa. The results showed that the dispersion state depends on the function of sonication time and temperature, and graphene has a significant reinforcement effect on epoxy.